Phlebectomy: Indications outside lower limb venous disease - Ramelet, Anne-Sylvie (2012)
Phlebectomy that is described by Muller has long been the ground for the treatment of lower limbs varicose veins. By analogy, the technique has had many other indications in venous conditions (eyelids, chest, abdomen, dorsum of the hands, arm and forearm), nonvenous in origin, such as in (subcutaneous cysts, venous lake, filling material and retrieval of hormonal implants). These particular indications of phlebectomy require not only a great mastering of the technique, but also a sound knowledge of anatomical pitfalls related to specific locations. Patients' expectations, particularly when the indications are purely for cosmetic reasons, can perfectly be unreasonable and the treating physician should be cautious and realistic about the outcome.